2015
DOI: 10.1097/mph.0000000000000187
|View full text |Cite
|
Sign up to set email alerts
|

Hemophilic Pseudotumor

Abstract: Hemophilic pseudotumor is a rare complication of hemophilia. We present the case of a male toddler with moderate hemophilia A and cranial hemophilic pseudotumor managed with factor VIII infusions. We also provide a review of the literature. Recognition of this rare manifestation of this complication of hemophilia is important to provide correct treatment and avoid unnecessary investigations, particularly biopsy, which is contraindicated in this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Doyle et al evaluated the available HPT treatment options associated with haemophilia [ 67 ]. The authors collected 48 articles: 40 single case reports, seven single centre case series, and one multicentre case series [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. They concluded that “timely surgical intervention with adequate haemodynamic support and the consideration of adjuvant therapies in selected cases can achieve acceptable outcomes in this cohort of patients”.…”
Section: Resultsmentioning
confidence: 99%
“…Doyle et al evaluated the available HPT treatment options associated with haemophilia [ 67 ]. The authors collected 48 articles: 40 single case reports, seven single centre case series, and one multicentre case series [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. They concluded that “timely surgical intervention with adequate haemodynamic support and the consideration of adjuvant therapies in selected cases can achieve acceptable outcomes in this cohort of patients”.…”
Section: Resultsmentioning
confidence: 99%